Improving the Understanding of Taharah Material in Students of MTS Negeri 4 Aceh Tengah through Active Learning Methods - Winarti; Gusriani, Wira; Winda; Sugiarti, Wiwi; Wiwie (MANDAILING GLOBAL EDUKASIA, 2025)
Students' understanding of taharah material is an important aspect in learning Islamic religious education, especially at the madrasah level. This study aims to improve students' understanding of MTsN 4 Aceh Tengah on taharah material through the application of active learning methods. This study uses a classroom action research (CAR) method which is carried out in several cycles. Data collection techniques include observation, interviews, and student understanding tests. The active learning methods applied include group discussions, simulations, and direct practice in understanding the concept of taharah. The results of the study showed that the use of this method significantly increased student involvement in the learning process and deepened their understanding of the concept of taharah. In addition, active learning methods also have a positive impact on student learning motivation, making them more enthusiastic and confident in understanding and applying the material taught. This increase can be seen from the evaluation results which show an increase in student understanding scores from the first cycle to the last cycle. Thus, active learning methods can be used as an effective strategy in improving the quality of learning taharah material in madrasahs. The application of this method is expected to be a reference for educators in developing more interactive and meaningful learning.